Lactiplantibacillus plantarum AR113 alleviates microbiota dysbiosis of tongue coating and cerebral ischemia/reperfusion injury in rat - Zhiqiang Xiong; Gang Liu; Ling Fang; Xiuming Li; Yongjun Xia; Guangqiang Wang; Xin Song; Lianzhong Ai (Food Science and Human Wellness)
Stroke is one of the leading causes of death and disability worldwide. However, information on stroke-related tongue coating microbiome (TCM) is limited, and whether TCM modulation could benefit for stroke prevention and rehabilitation is unknown. Here, TCM from stroke patients (SP) was characterized using molecular techniques. The occurrence of stroke resulted in TCM dysbiosis with signif icantly reduced species richness and diversity. The abundance of Prevotella, Leptotrichia, Actinomyces, Alloprevotella, Haemophilus, and TM7_[G-1]were greatly reduced, but common infection Streptococcus and Pseudomonas were remarkably increased. Furthermore, an antioxidative probiotic Lactiplantibacillus plantarum AR113 was used for TCM intervention in stroke rats with cerebral ischemia/reperfusion (I/R). AR113 partly restored I/R induced change of TCM and gut microbiota with significantly improved neurological deficit, relieved histopathologic change, increased activities of antioxidant enzymes, and decreased contents of oxidative stress biomarkers. Moreover, the gene expression of antioxidant-related proteins and apoptosis-related factors heme oxygenase-1 (HO-1), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), nuclear factor erythroid 2-related factor 2 (Nrf2), NAD(P)H:quinone oxidoreductase-1 (NQO-1), and Bcl-2 was significantly increased, but cytochrome C, cleaved caspase-3, and Bax were markedly decreased in the brain by AR113 treatment. The results suggested that AR113 could ameliorate cerebral I/R injury through antioxidation and anti-apoptosis pathways, and AR113 intervention of TCM may have the application potential for stroke prevention and control.